2015
DOI: 10.1051/0004-6361/201526092
|View full text |Cite
|
Sign up to set email alerts
|

The third release of the Large Quasar Astrometric Catalog (LQAC-3): a compilation of 321 957 objects

Abstract: Context. From an astrometric point of view, quasars constitute quasi-ideal reference objects in the celestial sphere, with an a priori absence of proper motion. Since the second release of the Large Quasar Astrometric Catalog (LQAC), a large number of quasars have been discovered, in particular with the upcoming new release of the SDSS quasars catalog. Aims. Following the same procedure as in the two previous releases of the LQAC, our aim was to compile all the quasars recorded until the present date, with acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…There are several noticeable features in this figure: (i) for the MKDP IMF, UCDs with initial stellar mass M UCD 10 8 M are as bright as quasars (Dunlop et al 1993(Dunlop et al , 2003Souchay et al 2015) for the first few 10 7 yr. We use low-redshift quasars because for these we were able to find bolometric luminosities, but also absolute magnitudes in the V and I band. We note, however, that high redshift quasars show very comparable luminosities as shown for example by Mortlock et al (2011).…”
Section: Evolution Of the Bolometric Luminosity With Timementioning
confidence: 91%
See 3 more Smart Citations
“…There are several noticeable features in this figure: (i) for the MKDP IMF, UCDs with initial stellar mass M UCD 10 8 M are as bright as quasars (Dunlop et al 1993(Dunlop et al , 2003Souchay et al 2015) for the first few 10 7 yr. We use low-redshift quasars because for these we were able to find bolometric luminosities, but also absolute magnitudes in the V and I band. We note, however, that high redshift quasars show very comparable luminosities as shown for example by Mortlock et al (2011).…”
Section: Evolution Of the Bolometric Luminosity With Timementioning
confidence: 91%
“…We have not found any publication or catalogue presenting both the absolute magnitudes in the V filter, M V , and I filter, M I . Therefore, the data in the table use the catalogue by Souchay et al (2015) containing the M I values. The M V values are taken from Dunlop et al (1993) and Dunlop et al (2003).…”
Section: Statistical Importancementioning
confidence: 99%
See 2 more Smart Citations
“…The newly released third Large Quasars Astrometric Catalog (hereafter LQAC3, Souchay et al 2015) includes most of the confirmed quasars. We cross-matched APOP with LQAC3 and estimated the zero-point as a comparison.…”
Section: Proper Motion Criteriamentioning
confidence: 99%